2023
DOI: 10.1186/s13058-023-01608-5
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic alterations underlying metaplasia into specific metaplastic components in metaplastic breast carcinoma

Abstract: Background Metaplastic breast carcinoma (MpBC) typically consists of carcinoma of no special type (NST) with various metaplastic components. Although previous transcriptomic and proteomic studies have reported subtype-related heterogeneity, the intracase transcriptomic alterations between metaplastic components and paired NST components, which are critical for understanding the pathogenesis underlying the metaplastic processes, remain unclear. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…New discoveries regarding the mechanisms [35,36], biomarkers [12], and expression patterns [37] of breast cancer are emerging with the use of intrinsic subtyping tools, speci cally the commonly used PAM50 and AIMS models. However, misclassi cation of intrinsic subtypes could result in decreased research accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…New discoveries regarding the mechanisms [35,36], biomarkers [12], and expression patterns [37] of breast cancer are emerging with the use of intrinsic subtyping tools, speci cally the commonly used PAM50 and AIMS models. However, misclassi cation of intrinsic subtypes could result in decreased research accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Huang-Chun Lien and colleagues (2023) categorized transcriptomic alterations underlying metaplasia into specific metaplastic components in MpBCs [56]. They conducted a gene expression profiling analysis on 59 micro-dissected samples using the NanoString BC360 Panel.…”
Section: Molecular Aspects In Metaplastic Breast Carcinoma: Associate...mentioning
confidence: 99%
“…Using the NanoString, Lieu et al ( 2023) demonstrated that cases with prominent spindle components showed an enrichment of macrophage signatures, and the upregulation of genes PD-L2 (also called PDCD1LG2) and B7-H3 that are associated with immune inhibitory pathways [56]. On the other hand, spindle components showed the downregulation of the TIGIT gene, which is related to immune activity.…”
Section: Tumor Immune Microenvironmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Metaplastic breast carcinomas have a high degree of genomic instability and display intricate patterns of copy number variations. 11 Compared with TNBC, MpBCs typically harbor significantly more mutations in TP53 (59% vs. 51%), PIK3CA (23% vs. 9%), and other members of the PI3K pathway (41% vs. 18%), 4 present genetic alterations in the Wnt pathway, 11,[15][16][17][18] and demonstrate CDKN2A loss, 11,19 EGFR overexpression and amplification, 11 MYC amplification, 20 TERT promoter hotspot mutations and gene amplification, 10,16,21 the enrichment of angiogenic genes, 22 and changes in genes related to the cell cycle 23 (Table 1). Furthermore, no differences between MpBCs and non-Mp TNBCs in the domains frequently mutated in either TP53 or PIK3CA, showing they have similar genetic alterations.…”
Section: Genetic Characteristicsmentioning
confidence: 99%